2006
DOI: 10.1007/s10856-006-0016-y
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion degradation and prevention by surface modification of biometallic materials

Abstract: Metals, in addition to ceramics and polymers, are important class of materials considered for replacement of non-functional parts in the body. Stainless steel 316, titanium and titanium alloys, Co-Cr, and nitinol shape memory alloys are the most frequently used metallic materials. These alloys are prone to corrosion in various extents. This review briefly discusses the important biomaterials, their properties, and the physiological environment to which these materials are exposed. Corrosion performance of curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
144
0
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(155 citation statements)
references
References 256 publications
1
144
0
10
Order By: Relevance
“…[18][19][20] To date, surgical stainless steel 316L (SS) is one of the most frequently used biomaterials because of a favorable combination of strength, good fabrication properties, low inherent toxicity, minimal reactivity with biomolecules, and cost efficiency when compared with other metallic implant materials. 1,21 The aims of this study were firstly, to investigate whether human monocytes are able to grow on SS implants and differentiate into mature OC. Secondly, to test the hypothesis that mature OC are able to directly corrode SS and release corresponding metal ions into the peri-implant environment, which may subsequently induce inflammatory reactions.…”
mentioning
confidence: 99%
“…[18][19][20] To date, surgical stainless steel 316L (SS) is one of the most frequently used biomaterials because of a favorable combination of strength, good fabrication properties, low inherent toxicity, minimal reactivity with biomolecules, and cost efficiency when compared with other metallic implant materials. 1,21 The aims of this study were firstly, to investigate whether human monocytes are able to grow on SS implants and differentiate into mature OC. Secondly, to test the hypothesis that mature OC are able to directly corrode SS and release corresponding metal ions into the peri-implant environment, which may subsequently induce inflammatory reactions.…”
mentioning
confidence: 99%
“…Hardy & Kendall (2005) have reported that particle diameters ranging from 25 to 100 mm are expected to follow the extracellular route, as their momentum is insufficient to breach the target barrier, due to the combination of relatively low density and small size. It has been recommended that stainless steel or polymer micro-particles should be used for extracellular routes, due to their biocompatibility and low cost (Disegi & Eschbach, 2000;Binyamin et al, 2006;Singh & Dahotre, 2007;Soliman, 2011;Sung et al, 2011).…”
Section: Micro-particle Materials and Sizementioning
confidence: 99%
“…Porous metals that are commonly used for biomedical applications are titanium and titanium alloys, Cobalt Chrome and nitinol shape memory alloys and stainless steel 316L [1]. Amongst all, stainless steel 316L is the longest being applied in the biomedical implant which is since 1920's [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Amongst all, stainless steel 316L is the longest being applied in the biomedical implant which is since 1920's [1,2]. Stainless steel 316L are low cost, easy availability and processing, good workability, high fatigue life and fracture toughness [1,3,4].…”
Section: Introductionmentioning
confidence: 99%